A 0.13μm inductively degenerated cascode CMOS LNA at 2.14GHz - Muhamad, M.; Soin, N.; Ramiah, H.; Noh, N.M.; Keat, C.W. (2011)
A 130-nm CMOS low-noise amplifier (LNA) for WCDMA applications is presented. The circuit adopts an inductively degenerated cascode topology. A detailed methodology using power constraint noise optimization (PCNO) method that leads to an optimum width of the LNA is presented. A theoretical noise figure optimization using fixed power was used as a design optimization guide. This inductively degenerated cascade topology show good noise performance which it achieve a noise figure of 1.32dB while provides a forward gain, S21 of 18.24 dB from a 1.2V voltage supply. The input reflection coefficient, S11 is -19 dB.